Are changes in pain intensity related to changes in balance control in individuals with chronic non-specific low back pain? A systematic review and meta-analysis - Daniel K.Y. Zheng; Jae Q.J. Liu; Jeremy R. Chang; Jeffrey C.Y. Ng; Zhixing Zhou; Jinlong Wu; Chelsia K.C. Cheung; Frank F. Huang; Sabina M. Pinto; Dino Samartzis; Manuela L. Ferreira; Kanchana Ekanayake; et al. (Journal of Sport and Health Science)
Purpose: The aim of this study was to summarize the evidence regarding whether pain reduction in individuals with chronic non-specific low back pain (CNSLBP) following conservative interventions is related to corresponding improvements in balance control. Methods: Randomized controlled trials were identified from 5 databases (MEDLINE, Cochrane Library, Embase, Web of Science, and PsycINFO). Two reviewers independently screened and identified relevant studies that investigated the effects of non-surgical or non-pharmacological CNSLBP treatments on both pain intensity and balance control. Meta-regression analyses were performed to establish the associations between post-treatment changes in these 2 variables. Results: Thirty one studies involving 1280 participants with CNSLBP were included. Moderate-quality evidence suggested that pain reduction was associated with and explained 34%–45% of decreases in body sway, as measured by center-of-pressure (CoP) area and CoP velocity with eyes open. However, no significant association was observed between pain reduction and CoP area or velocity in anteroposterior/mediolateral directions. Similarly, there was no significant association between pain reduction and CoP distance or radius. Low-quality evidence indicated that pain relief explained a 15% improvement in one-leg stance with eyes open but not in the eyes-closed condition. Additionally, very low-quality evidence suggested that pain relief explained a 44% decrease in the static anteroposterior stability index with eyes closed but not in the eyes-open, mediolateral, or overall conditions. Furthermore, low-quality evidence indicated that reduced pain was associated with and accounted for 25%–43% of the improved composite and posteromedial scores of the star-excursion balance test, rather than the anterior and posterolateral scores. Conclusion: Depending on the type of balance assessment, pain relief following conservative interventions may slightly to moderately enhance balance control in individuals with CNSLBP. Clinicians should pay close attention to the balance control in patients with CNSLBP, particularly among older adults.